2010
DOI: 10.17305/bjbms.2010.2652
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Filtration Rate in Examined Population of Bosnian Posavina - Region of Balkan Endemic Nephropathy

Abstract: Balkan endemic nephropathy (BEN) is chronic tubulointersticial nephritis of unknown aetiology characterized by an insidious onset and gradual progression to end stage renal disease (ESRD). Endemic regions of Bosnia and Herzegovina are Posavina and Semberija, sited at basin of Sava River. In BEN, just like in other chronic renal diseases (CKD), glomerular filtration rate (GFR), is assumed a marker of overall renal function. The aim of this study was to compare GFR in examinees of endemic and non-endemic region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Intermittent proteinuria indicating proximal tubular damage can be found early, whereas in the uraemic stage of BEN, it becomes permanent. Loss of urine concentration capacity precedes a decrease in the glomerular filtration rate (Alecković et al 2010 ; Arsenović et al 2005 ; Dimitrov et al 2006 ).…”
Section: Epidemiology Pathology Clinical Features and Diagnosis Of mentioning
confidence: 99%
“…Intermittent proteinuria indicating proximal tubular damage can be found early, whereas in the uraemic stage of BEN, it becomes permanent. Loss of urine concentration capacity precedes a decrease in the glomerular filtration rate (Alecković et al 2010 ; Arsenović et al 2005 ; Dimitrov et al 2006 ).…”
Section: Epidemiology Pathology Clinical Features and Diagnosis Of mentioning
confidence: 99%
“…The urinary sediment shows sparse white and red blood cells. In the early stages of BEN, the loss of urine concentration capacity precedes the decline in the glomerular filtration rate [ 15 17 ]. Serum proteins and immunoglobulins are unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Authors concluded that average kidney volume was bellow referent borderline values in all patients, even in the group (11 patients) with average GFR of 120.65 mL/min [ 22 ]. Twenty years later, as a part of our screening in endemic village Domaljevac, estimated GFR was found in the normal ranges regardless of family history of BEN [ 23 ].…”
Section: Discussionmentioning
confidence: 99%